A nomenclatural synopsis of the genus Triplaris (Polygonaceae) - Koenemann, Daniel Mark; Burke, Janelle M. (Phytotaxa, 2025)
Triplaris (Polygonaceae) is a genus of fast-growing dioecious trees, containing 18 biological species. Despite a recent taxonomic revision, many of the names in the genus still need typification. The present work had three major goals: 1) to list all putatively published names in Triplaris, 2) to typify the untypified names, and 3) to refine type locality information for a number of the rare species in the genus, in order that the type localities might be later revisited and these rare species be better known. We recovered 98 names (at the specific and subspecific rank). Eleven of these names are now recognized as Ruprechtia species by Brandbyge (1986) or Pendry (2004). We here designated 24 types, including: 17 lectotypes (Blochmannia weigeltiana, Magonia scandens, Triplaris americana, T. arnottiana, T. auriculata, T. caracasana var. vargasii, T. estriata, T. gardneriana, T. noli-tangere, T. pachau var. longipetala, T. pachau var. pachau, T. pavonii, T. poeppigiana, T. pyramidalis, T. schomburgkiana, T. surinamensis var. chamissoana, Vellasquezia melaenodendron), 3 epitypes (T. auriculata, T. pyramidalis, Vellasquezia melaenodendron), and 4 neotypes (T. brasiliana, T. caracasana var. caracasana, T. cumingiana, T. martiana var. martiana). Concerning two species (T. paraguayensis and T. riedeliana), we have left the type specimens undesignated until original material is discovered.